The effect of rotary instrumentational speeds on foraminal deformation: An in vitro study - Burçin Arıcan; Betül Aycan Uysal (Saudi Endodontic Journal)
Introduction: The effect of the rotational speed on the performance of endodontic therapies has been unclear. This study aimed to evaluate the foraminal deformation (FD) caused by two rotary instrument systems with different rotational speeds at three different working length determinations using Scanning electron microscopy is better (SEM). Materials and Methods: Sixty mesiobuccal root canals of maxillary molars were randomly divided into two groups (n = 30 each) and instrumented using either RaCe®Evo (at 1000 rpm and 1 Ncm torque) or TruNatomy (at 500 rpm and 1.5 Ncm torque) 1 mm behind the major foramen (MF) (n = 10), at the MF (n = 10), and 1 mm beyond the MF (n = 10). The roots were scanned under SEM at × 300 magnification and 15.00 kV before and after instrumentation procedures. The pre- and postoperative SEM images were analyzed using the ImageJ software program. The FD was represented with the circularity and Feret’s diameter ratio of the apical foramen. Results: No significant difference was observed in the before and after values of the circularity and Feret’s diameter parameters within and between the rotary instrument groups (P > 0.05). Conclusion: Increasing of the rotational speed had no negative effect on the FD.